The Influence of Teamwork and Work Discipline on Employee Performance at the Ms Butik Karawang Store - Effendi, Dicky Wahyu; Isyanto, Puji; Yani, Dini (PT FORMOSA CENDEKIA GLOBAL, 2024)
The influence of cooperation and work discipline on the productivity of MS Butik Karawang employees is the subject of this research. Finding out how successful staff performance is is the reason for conducting this research. The descriptive methodology of this research focuses on the influence of cooperation and work discipline on productivity in the workplace. Information collected from MS Butik Karawang staff members was used. Questionnaires were given to staff and interviews were conducted with MS Boutique shop owners to collect data. Using SPSS 22, researchers carried out validity and reliability tests, as well as t tests and f tests on the data used in the research. Research findings reveal that the operational performance of MS Butik Karawang store personnel is significantly influenced by work discipline and cooperation.